Phosphomimetic mutation of the N-terminal lid of MDM2 enhances the polyubiquitination of p53 through stimulation of E2-ubiquitin thioester hydrolysis - Fraser, Jennifer A; Worrall, Erin G; Lin, Yao; Landre, Vivien; Pettersson, Susanne; Blackburn, Elizabeth; Walkinshaw, Malcolm; Muller, Petr; Vojtesek, Borek; Ball, Kathryn; Hupp, Ted R (Journal of molecular biology, 2015)
Mouse double minute 2 (MDM2) has a phosphorylation site within a lid motif at Ser17 whose phosphomimetic mutation to Asp17 stimulates MDM2-mediated polyubiquitination of p53. MDM2 lid deletion, but not Asp17 mutation, induced a blue shift in the λ(max) of intrinsic fluorescence derived from residues in the central domain including Trp235, Trp303, Trp323, and Trp329. This indicates that the Asp17 mutation does not alter the conformation of MDM2 surrounding the tryptophan residues. In addition, Phe235 mutation enhanced MDM2 binding to p53 but did not stimulate its ubiquitination function, thus uncoupling increases in p53 binding from its E3 ubiquitin ligase function. However, the Asp17 mutation in MDM2 stimulated its discharge of the UBCH5a-ubiquitin thioester adduct (UBCH5a is a ubiquitin-conjugating enzyme E2D 1 UBC4/5 homolog yeast). This stimulation of ubiquitin discharge from E2 was independent of the p53 substrate. There are now four known effects of the Asp17 mutation on MDM2: (i) it alters the conformation of the isolated N-terminus as defined by NMR; (ii) it induces increased thermostability of the isolated N-terminal domain; (iii) it stimulates the allosteric interaction of MDM2 with the DNA-binding domain of p53; and (iv) it stimulates a novel protein-protein interaction with the E2-ubiquitin complex in the absence of substrate p53 that, in turn, increases hydrolysis of the E2-ubiquitin thioester bond. These data also suggest a new strategy to disrupt MDM2 function by targeting the E2-ubiquitin discharge reaction.
Keywords: Hydrolysis; RING domain; polyubikvitin; ubikvitin konjugující enzymy; Humans; ubikvitinace; Polyubiquitin; hydrolýza; Molecular Sequence Data; molekulární sekvence - údaje; nádorový supresorový protein p53; sekvence aminokyselin; Protein Conformation; linear motifs; Proto-Oncogene Proteins c-mdm2; ubikvitin; lidé; zvířata; myši; allostery; Mice; protoonkogenní proteiny c-mdm2; Amino Acid Sequence; bodová mutace; Ubiquitination; aminokyselinové motivy; alosterická regulace; Point Mutation; nádorové buněčné linie; Ubiquitin-Conjugating Enzymes; Animals; Amino Acid Motifs; Cell Line, Tumor; ubiquitination; terciární struktura proteinů; MDM2; Protein Structure, Tertiary; Allosteric Regulation; Ubiquitin; konformace proteinů; Tumor Suppressor Protein p53